Utilization of Maternity Services and Its Relationship with Postpartum Use of Modern Contraceptives Among Women of Reproductive Age Group in Nigeria - Ugwu IA; Itua I (Dove Medical Press, 2020)
Innocent Anayochukwu Ugwu,1 Imose Itua2 1Department of Obstetrics & Gynecology, College of Medicine, Enugu State University of Science & Technology (ESUT) and ESUT Teaching Hospital, Enugu, Nigeria; 2Department of Public Health and Healthcare Management, University of Liverpool/Laureate Online Education, Liverpool, UKCorrespondence: Innocent Anayochukwu UgwuDepartment of Obstetrics & Gynecology, College of Medicine, Enugu State University of Science & Technology (ESUT) and ESUT Teaching Hospital, Parklane, Enugu, NigeriaTel +234 8034749789Email innocent.ugwu@esut.edu.ngBackground: Utilization of maternity services (UMS) exposes mothers to family planning (FP) counseling and other FP promotional activities. Uptake of postpartum modern contraceptives (PPMC) reduces both infant and maternal mortalities by reducing unwanted pregnancies and promoting good child spacing. Understanding the relationship between UMS and uptake of PPMC was therefore very important.Purpose: To determine the association between UMS and uptake of PPMC among women of the reproductive age group in Nigeria taking into consideration the influence of the place of access to the maternity services.Patients and Methods: This study was a descriptive epidemiological study design. Secondary data obtained from the 2013 Nigerian Demographic Health Survey (NDHS) was analyzed to achieve the above aim. The uptake of PPMC was the dependent variable (DV). The independent variables (IDV) selected were the number of antenatal care (ANC) visits, place of access of ANC, place of delivery, timing of postnatal care (PNC) and place of access of PNC. Other control variables include socio-demographic factors. Descriptive statistics, chi-square testing, and logistic regression analyses were conducted to determine the association between the PPMC uptake and the IDV/other control variables. Statistical significance was claimed at p<0.05.Results: Utilization of maternity services was associated with higher uptake of PPMC among the women (>/= 4 ANC visits OR = 2.08, 95% CI=1.65–2.62, P<0.001; public facility delivery OR= 1.80, 95% CI= 1.54–2.10, P< 0.001; private facility delivery OR =1.54, 95% CI 1.28–1.85, P< 0.001; PNC OR=1.21, 95% CI= 1.02–1.43, P=0.029). Accessing postnatal care in private health facilities was associated with increased uptake of PPMC (OR= 1.46, 95% CI =1.05–2.02, P= 0.024). The number of children alive, educational attainment, wealth index and having information about FP remained significant predictors of PPMC uptake.Conclusion: The utilization of maternity services was positively associated with postpartum use of modern contraceptives among women of reproductive age in Nigeria. There was increased uptake of PPMC among women who utilized maternity service compared to their counterparts who did not. Regarding the place of access, accessing antenatal care as well as delivering in either private or public health facilities was not a significant predictor of PPMC use. However, accessing postnatal care in private facilities was associated with higher uptake of PPMC.Keywords: maternity services, postpartum contraception, family planning, Nigeria